Mengungkap Keunikan Tafsir Aceh - Fauzi Saleh (Al-Ulum, 2012)
Aceh that well-known as â€œMecca Verandahâ€ has produced the ulemas with the great works. Acehâ€™s ulema considered as the first who wrote tafseer (Quranic interpretation) ini Malay language in South East Asia. The tafseer was composed by Abdurrauf al-Singkili. There were still many tafseer books written Acehâ€™s ulemas need to be explored. This paper will explained several of them and their unique substance. That is important to be mentioned that the ulemas wrote the tafseers in a book, part of the books, article, even mixed with other field of knowledge. The writer will also focuses on method and type of tafseer as Acehâ€™s ulama works. The creativity of ulemas can be traced through their books of tafseer such â€œTurjumunul Mustafid, an-Nur, Al-Qurâ€™anul Karim dan Terjemah Bebas Bersajak dalam Bahasa Acehâ€ etc. These tafseers generally had been written based on tahlili method. Meanwhile the type of tafseer that used consisted of fiqhi, sufi and also â€˜ilmi.